1989
DOI: 10.1016/0014-5793(89)81450-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Ca2+‐switch in skeletal and cardiac muscles

Abstract: To determine the significance of the global structure of the regulatory proteins in the mechanism of the Ca*+-switch in cardiac and skeletal muscle contractions, the properties of a family of Ca Z+-binding proteins with 4 or 3 EF-hand motifs have been studied with desensitized skinned fiber preparations. Proteins with 4 EF hands (such as troponins C -TnCs) are dumb-bell shaped, those with 3 EF hands (parvalbumin) being ellipsoidal. The number of active sites varied between four and two. We find that the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…4. In addition, in 100 mm salt, reconstituted fibres manifest Sr2" sensitivity curves characteristic of cardiac TnC (Babu, Lehman & Gulati, 1989). If cardiac TnC reconstitution had been partial, the force level with maximal activation (with Sr2+ or Ca2+) would have remained submaximal in both low and high salt concentrations.…”
Section: Reconstitution Controlsmentioning
confidence: 99%
“…4. In addition, in 100 mm salt, reconstituted fibres manifest Sr2" sensitivity curves characteristic of cardiac TnC (Babu, Lehman & Gulati, 1989). If cardiac TnC reconstitution had been partial, the force level with maximal activation (with Sr2+ or Ca2+) would have remained submaximal in both low and high salt concentrations.…”
Section: Reconstitution Controlsmentioning
confidence: 99%
“…But, Kerrick and colleagues (1981;1985;Hoar et ai., 1988) had maintained for several years that, in the fibre, the difference between cardiac and skeletal fibres involved complicated proteinprotein interactions outside their regulatory systems. Subsequently, Babu et al (1989) published the converse study where TnC was exchanged in psoas fibres, hoar and colleagues (1988) have now confirmed the results on cardiac muscle. When the indigenous cardiac TnC was replaced with fast skeletal TnC, Sr 2+-and Ca2+-sensitivity values were observed to fall to match the measurements on normal psoas fibre.…”
mentioning
confidence: 85%
“…This was suggested on the basis of results with parvalbumin and oncomodulin [25]. Parvalbumin lacks nearly half of the amino acid structure corresponding to the N-terminus lobe.…”
Section: Diverse Structure-function Specifications Of Cammentioning
confidence: 99%
“…This is associated with a collapsed central helix that folds the protein into an ellipsoidal configuration [1]. Parvalbumin neither binds to TnC-denuded sites in the fiber nor is active in Ca z+ regulation [25]. Oncomodulin is an analog of parvalbumin, but is apparently enzymatically active in solution in vitro [26,27].…”
Section: Diverse Structure-function Specifications Of Cammentioning
confidence: 99%
See 1 more Smart Citation